Influence of chromated copper arsenate type-C concentration on the quality of treated fence posts (Research, Society and Development, 2022)
This study aimed to reduce the concentration of chromated copper arsenate type-C (CCA-C) in preservative treatments of Eucalyptus sp. for use in applications with ground contact. The genetic materials used were Eucalyptus cloeziana of seminal origin and the clonal hybrid (E. urophylla x E. camaldulensis), which was derived from six year old crops at commercial plantations. The basic density, moisture content, percentage of sapwood, and wood treatable volume were determined, and the anatomical structures were characterized. The genetic materials were treated with concentrations of 1.2%, 1.3%, 1.4%, 1.5%, and 1.6% active ingredients (AI) of CCA-C. The quality of the preservative treatment was evaluated via penetration and retention tests. The treated wood volume of E. cloeziana exhibited 44% irregular partial penetration, 40% vascular penetration, 12% peripheral partial penetration, and 4% no penetration. For the hybrid, the wood volume exhibited 68% total penetration, 24% peripheral partial penetration, and 8% irregular partial penetration. The concentrations of 1.4% AI and 1.5% AI for E. cloeziana and of 1.4% AI and 1.6% AI for hybrid reached the minimum retention required by standard.